Pengaruh Literasi Keuangan Dan Digital Payment Terhadap Minat Belanja Mahasiswa: Kepercayaan Sebagai Variabel Mediasi - Selfianti Selfianti; Muryani Arsal; Ismail Badollahi (Owner : Riset dan Jurnal Akuntansi, 2025)
This study examines the influence of financial literacy and digital payment on students' shopping interest, with trust as a mediating variable. Using a quantitative approach with 116 postgraduate students from Universitas Muhammadiyah Makassar, data were analyzed through PLS-SEM. Results indicate that digital payment significantly affects shopping interest both directly (?=0.250, p<0.001) and indirectly through trust, while financial literacy shows no significant impact. These findings align with the Theory of Planned Behavior, where perceived behavioral control (digital payment ease) and trust shape behavioral intentions. The study addresses a critical gap by empirically validating trust's mediating role in fintech adoption among students, offering practical insights for digital payment providers to enhance security features and user experience.